Spark of the everflame eaudiobook - Cole, Penn (The Kindred's Curse, 2024)
When old secrets catch fire, everything will burn. In a mortal world colonized by the gods and ruled over by their cruel offspring, the Descended, Diem Bellator yearns to escape the insular life of her poor village. Her mother's sudden disappearance—and the discovery of a dangerous secret about her past—offer Diem an unexpected opportunity to enter the dark world of Descended royalty and unlock the web of mysteries her mother left behind. With the dying king's handsome, mysterious heir watching her every move and a ruthless mortal alliance recruiting her to join the growing civil war, Diem will have to navigate the unwritten rules of love, power, and politics in order to save her family—and all of mortal kind. Spark of the Everflame is the first book in The Kindred's Curse Saga, a four-book epic fantasy romance series that follows our feisty, bad*ss heroine Diem Bellator in her fight against injustice and oppression, her struggle to survive in a royal palace full of betrayal and intrigue, and her journey of self-discovery and finding true love. This slow-burn, enemies-to-lovers series is perfect for fans of unique magic systems, dragons and other mythical creatures, angst and romantic tension, and hilarious banter.